1996
DOI: 10.1074/jbc.271.48.30442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Paired Basic Convertases Implicated in HIV gp160 Processing Based on in Vitro Assays and Expression in CD4+ Cell Lines

Abstract: The human immunodeficiency virus HIV envelope glycoprotein gp160 is synthesized as an inactive precursor, which is processed into its fusiogenic form gp120/gp41 by host cell proteinases during its intracellular trafficking. Kexin/subtilisin-related endoproteases have been proposed to be enzyme candidates for this maturation process. In the present study, 1) we examined the ability of partially purified precursor convertases and their isoforms to cleave gp160 in vitro. The data demonstrate that all the converta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
130
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 59 publications
10
130
4
Order By: Relevance
“…With regard to the identification of this enzyme activity, furin is known to be quite active at neutral pH; it exhibits greater than 50% of maximal activity between pH 6.0 and 8.5 [20]. The convertases PC6 and PACE4 have a broad pH optimum with peak activity at neutral to weakly basic pHs (7.0-8.0 for PC6; 7.0-8.5 for PACE4) [21]. In contrast to these other convertases, PC1 active forms are active within a much narrower pH range; 87 kDa PC1 has an optimum pH between pH 5.5 and 6.5 [22] and 74/66 kDa PC1 displays an even narrower pH optimum (between 5.0 and 5.5) with significantly reduced activity at neutral pH [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the identification of this enzyme activity, furin is known to be quite active at neutral pH; it exhibits greater than 50% of maximal activity between pH 6.0 and 8.5 [20]. The convertases PC6 and PACE4 have a broad pH optimum with peak activity at neutral to weakly basic pHs (7.0-8.0 for PC6; 7.0-8.5 for PACE4) [21]. In contrast to these other convertases, PC1 active forms are active within a much narrower pH range; 87 kDa PC1 has an optimum pH between pH 5.5 and 6.5 [22] and 74/66 kDa PC1 displays an even narrower pH optimum (between 5.0 and 5.5) with significantly reduced activity at neutral pH [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to purify the intact zymogen from PC2-S383A-producing CHO-K1 cells co-expressing 21 kDa 7B2 should lead to a better understanding of its molecular structure including its interaction with 7B2, its complex activation mechanism, and the development of specific and potent PC2 inhibitors for therapeutic use. A. Sequence of the PC2 propeptide; Three potential cleavage sites within the proPC2 propeptide are shown in bold; the primary and secondary sites known to be cleaved [21] are indicated. B. Purified PC2 and PC2-S383A were incubated at pH 5.0 for the indicated times and were immunoblotted with PC2 antiserum.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a total of seven mammalian subtilisin-like proteases have been identified: furin (also called PACE), PCI (PC3), PC2, PACE4, PC4, PC5-A (PC6-A) and its isoform PC5-B (PC6-B) and the newly discovered PC7 (PC8, LPC or SPC7) (for reviews and updates [6][7][8][9]). While furin is ubiquitously expressed, PC7, PACE4 and PC5 exhibit a widespread tissue distribution, and all catalyze the processing of precursors within the constitutive secretory pathway [6][7][8][9][10][11]. In addition, we recently showed that immune cells express large amounts of both furin and PC7 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in cellular coexpression experiments, furin was shown to catalyze the proteolytic processing of Newcastle disease virus F protein [16], parainfluenza virus type 3 HA protein [17] and cytomegalovirus gpUL55 protein [18], and furin, PACE4 [19,20] and PC7 [10] cleave HIV-1 gpl60. In vitro experiments have demonstrated that furin, PACE4, PC5 as well as PCI can cleave the HIV-1 gpl60 into gpl20/gp41 [10,11,20,21]. Although these results suggest that a certain redundancy exists in the ability of mammalian convertases to process viral envelope glycoproteins, quantitation of the level of expression of the PCs in virus-infectable host cells should be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation